Higher prevalence of peripheral arterial disease in Ghana compared to Ghanaian migrants in Europe: the RODAM study - Hayfron-Benjamin, Charles F.; van den Born, Bert-Jan; Maitland-van der Zee, Anke H.; Amoah, Albert G. B.; van der Linden, Eva L.; Stronks, Karien; Klipstein-Grobusch, Kerstin; Bahendeka, Silver; Danquah, Ina; Beune, Erik; Smeeth, Liam; Agyemang, Charles (International journal of cardiology, 2020)
Background - Evidence suggests that the burden of peripheral artery disease (PAD) is rising more rapidly than other forms of cardiovascular diseases in sub-Saharan Africa, but the extent to which they differ between rural and urban settings in Africa and upon migration to Europe is unknown. We assessed the burden of PAD among Ghanaians living in rural- and urban-Ghana and Ghanaian migrants living in three European countries. - Methods - Cross-sectional analyses of baseline data from the multicenter Research on Obesity and Diabetes among African Migrants (RODAM) study were done. Data from 5516 participants living in Europe (1487 Amsterdam, 546 Berlin, 1047 London) and Ghana [1419 urban and 1017 rural] aged 25-70years were included. PAD was defined as ankle brachial index≤0.90. Comparisons among sites were made using logistic regression analysis. - Results - The age-standardized prevalence of PAD was higher in Ghanaians living in rural [7.52%, 95% CI = 5.87-9.51] and urban [8.93%, 7.44-10.64] Ghana than for their compatriots living in Europe [5.70%, 4.35-7.35 for London; 3.94%, 2.96-5.14 for Amsterdam; and 0.44%, 0.05-1.58 for Berlin]. The differences persisted even after adjustment for age, sex, education and the conventional cardiovascular risk factors [adjusted odds ratio = 3.16, 95% CI = 2.16-4.61, p < .001 for rural-Ghana; and 2.93, 1.87-4.58, p < .00 for urban-Ghana, compared with Ghanaian migrants in Europe]. - Conclusions - Our study shows that Ghanaians living in Ghana have higher prevalence of PAD than their migrant compatriots. Further work is needed to identify potential factors driving the high prevalence of PAD among non-migrant Ghanaians to assist interventions aimed at reducing PAD burden.